The Effect Of Workload And Work Discipline On Turnover Intention Among Sales Division Employees Of PT. Kendaraan Titipan Surabaya - Tariska Saffa Devani; Endang Iryanti (STIE Amkop Makassar, 2026)
Turnover among sales division employees at a used vehicle trading company in Surabaya has climbed steadily over the past threee years, mirrrored by a parallel rise in employee absenteeism during the same period.This condition is presumed to be linked to the work pressure carried by sales personnel and a decline in compliance with workplace rules. This study was designed to examine the influence of workload and work discipline on employees’ turnover intention within that sakes division. An associative quantitative approach was applied census (saturated sampling) technique. The collected data were then processed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using, SmartPKS software. The results show that workload has a positive and significant effect on turnover intention, whereas work discipline shows a negative direction of influence that is not yet satistically significant. Together, both variables account for 30,3% of the variance in turnover intention. These findings suggest that managing working time demands should become a priority for the company in curbing employess intention to leave, while reinforcing compliance with working hours remains worth maintaining as a supporting, though not dominant, factor in employee retention.